Philosophy of administration for the twenty-first century - Seshadri, K. (1996)
Discussing grim socio-political and administrative realities which characterise our political life and administrative system today, the author makes a strong plea for encashing the opportunity of reconstructing our national economy under the present globalisation regime through applying necessary correctives. - Reproduced
Keywords: Public administration